THE CORRELATION BETWEEN EFL STUDENTS’ VOCABULARY ACHIEVEMENT AND ENGLISH-SPEAKING ABILITY - Kadek Nandya Susmitha Arcani Dewi; Dewa Ayu Ari Wiryadi Joni; Anak Agung Putu Arsana (Academic Journal on English Studies (AJOES), 2023)
The research aims at finding out the correlation between vocabulary achievement and speaking ability of eighth grade students of SMP Pancasila Canggu. There were 38 students were used as the sample. The instruments used were filling in the blanks test for vocabulary test and map-cued test for speaking performance. The data collected in this research was analyzed by using Pearson Product Moment Correlation in SPSS Statistics 23 version. It was found that r was 0.447. It shows that there was a significant correlation between students’ vocabulary achievement and speaking ability of eighth grade students of SMP Pancasila Canggu. Based on r table, the table of r score 0.400-0.600 is a moderate level. It means there is a positive correlation between vocabulary achievement and speaking ability.